Oxidative Stress Modifies the Levels and Phosphorylation State of Tau Protein in Human Fibroblasts - Ibáñez-Salazar, Alejandro; Bañuelos-Hernández, Bernardo; Rodríguez-Leyva, Ildefonso; Chi-Ahumada, Erika; Monreal-Escalante, Elizabeth; Jiménez-Capdeville, María E.; Rosales-Mendoza, Sergio (Frontiers in Neuroscience, 2017)
Since the tau protein is closely involved in the physiopathology of Alzheimer´s disease (AD), studying its behavior in cellular models might lead to new insights on understanding this devastating disease at molecular levels. In the present study, primary cultures of human fibroblasts were established and used to determine the expression and localization of the tau protein in distinct phosphorylation states in both untransfected and tau gene-transfected cells subjected to oxidative stress. Higher immunopositivity to phospho-tau was observed in cell nuclei in response to oxidative stress, while the levels of total tau in the cytosol remained unchanged. These findings were observed in both untransfected cells and those transfected with the tau gene. The present work represents a useful model for studying the physiopathology of AD at the cellular level in terms of tau protein implications.